Competências do preceptor enfermeiro: uma análise da percepção de enfermeiros de uma instituição hospitalar privada - Miyazato, Helena Scaranello Araújo (2015)
This study had as objective to analyze, in the perception of nurses, the necessary competences to the preceptory of nurses in a hospital institution. It's a qualitative research, with descriptive and exploratory character. The study was accomplished in a medium-sized hospital in Marilia-SP. The data were collected by a semi-structured interview with the nurses who work on the hospital institution in the nurse function, of both genders, who agreed with the research objective and signed the Free and Informed Consent Term. The interviews were recorded, transcribed and analyzed using the content analysis technique, thematic modality. The study is in consonance with the ethical principles of research and had an authorization granted by the Ethics Committee on Research of the Federal University of São Paulo, by CAAE: 41473814.3.3001.5496 and number of the opinion: 992.076. When the respondents defined 'preceptor', they attributed characteristics instead of defining them. The data show that the preceptor nurses must equip themselves with vast technical and scientific knowledge to prepare to be a formator of other professionals in nursing, however, there's a need for specific capacity to act in education, due to the variety of roles that the teacher must execute: facilitator of students learning, planner of courses, advisor of individuals or groups, producer of educational material, evaluator of learning and model of professional behavior. The nurse preceptor should be an example of professional, responsible, patient and base their actions on respect for the students' individuality, with the finality to promote the articulation between teaching, service and learning. From the analysis and categorization of the interviews, a matrix with competences was built to map the profile of preceptor nurses who work in admission training. The definition of the assignments of nurse preceptor may contribute to the permanent education of the professionals who are in the working world and weren't formed based on the National Curriculum Guidelines, in order to qualify them for the resolutivity of current demands and to the improvement of the quality of care in health. In front of this scenario, the challenge of health institutions is to choose professionals or empower them to exercise preceptory of newly hired nurses, adjusting the nursing assistance to the real needs of users.